Successful use of extracorporeal membrane oxygenation for airway‐obstructing lung adenocarcinoma. Issue 10 (26th August 2020) - Kitazawa, Shinsuke; Kobayashi, Naohiro; Ueda, Sho; Enomoto, Yuki; Inoue, Yoshiaki; Shiozawa, Toshihiro; Sekine, Ikuo; Kawai, Hitomi; Noguchi, Masayuki; Sato, Yukio
Abstract : Endobronchial‐invasive lung cancers are generally diagnosed at advanced stages and may require emergency treatment for airway obstruction. Stent implantation is a common intervention for such obstructed airways but certain subsets of patients cannot receive adequate treatment without respiratory support. Veno‐venous extracorporeal membrane oxygenation (ECMO) is a salvage therapy for respiratory failure but its usefulness in managing patients with advanced lung cancer remains unclear given the poor prognosis. In recent years, molecular targeted agents for patients with driver mutations offer rapid responses and may be administered even while under critical care. In this report, we describe the case of 39‐year‐old female who presented to our emergency department with severe respiratory distress. A computed tomography scan revealed a large mediastinal tumor invading the tracheal carina causing severe stenosis of the left main bronchus and right main pulmonary artery. ECMO support was required as the respiratory condition remained unstable despite high pressure ventilation. Under ECMO support, the patient underwent bronchial stent implantation and was successfully weaned off ECMO. The tumor was histologically diagnosed as pulmonary adenocarcinoma with anaplastic lymphoma kinase gene rearrangement. Treatment with a tyrosine kinase inhibitor, alectinib, induced a marked tumor reduction within a short period. The patient recovered well and is now in remission one year later. This case indicates that intensive respiratory support with ECMO may become a bridge through the critical period for selected patients with respiratory failure secondary to advanced lung cancer. Key points: Significant findings of this study: ECMO was important to maintain oxygenation during airway intervention for acute respiratory failure due to critical lung adenocarcinoma with ALK gene rearrangement. What this study adds: With the development of targeted therapies and the improvement in therapeutic bronchoscopy, intensive respiratory support with ECMO may be helpful especially in selected lung cancer patients with oncogenic driver mutations. Abstract : Respiratory support with extracorporeal membrane oxygenation (ECMO) in managing patients with advanced lung cancer remains unclear given the poor prognosis. Targeted agents for patients with driver mutations offer rapid responses and may be administered even while under critical care. In some patients with critical lung cancer, ECMO may become a bridge through the critical period with respect to effective anti‐cancer therapies.